FOREIGN INVESTMENT AND REGIONAL DEVELOPMENT VISION; (REVIEW OF WIDI INTERNATIONAL FISHING TOURNAMENT-WIFT 2017 EVENTS) - Nurcholish Rustam (IAIN Ternate, 2020)
The development of investment in Indonesia is an indicator of the progress of economic growth in Indonesia. Investments made correctly can support the improvement of the welfare of the Indonesian people. One of the challenges in implementing investment in Indonesia is the implementation of regional autonomy in Indonesia. The era of regional autonomy in Indonesia began in 2001 after the enactment of Law no. 22 of 1999 concerning Regional Government and later updated by Law no. 32 of 2004. Meanwhile, the source of funding is regulated in Law no. 25 of 1999 concerning Financial Balance between the Central Government and Local Government, which was later updated by Law no. 33 of 2004. The important meaning of this regulation is that there is a system of financial distribution that is fair, proportional, democratic, transparent and efficient in the framework of implementing decentralization by taking into account the potential, conditions and needs of the regions as well as the amount of funding for the implementation of deconcentration and co-administration. In the context of such regulations on regional autonomy, the management of management resources through regional potentials through leading sectors such as tourism, fisheries, agriculture and other potentials is also regulated. Widi International Fishing Tournament (WIFT) 2017 is one of the instruments to drive the people's economy. Of course, the roles of local governments and the private sector are very important through breakthroughs in medium and long term programs that are in line with the regional development vision. Keywords: foreign investment, regional development